Association of the KCNJ5 gene with Tourette Syndrome and Attention‐Deficit/Hyperactivity Disorder. (19th June 2014) - Gomez, L.; Wigg, K.; Zhang, K.; Lopez, L.; Sandor, P.; Malone, M.; Barr, C. L.
Abstract : Linkage and association of Tourette Syndrome (TS) and Attention‐Deficit/Hyperactivity Disorder (ADHD) have previously been reported in the 11q24 chromosomal region. To identify the risk gene within the region we studied the potassium inwardly‐rectifying channel J5 ( KCNJ5 ) gene in a sample of 170 nuclear families with TS. We genotyped eight markers across the gene and observed biased transmission of haplotypes from parents to probands in this sample. We then tested these markers in an independent sample of 242 nuclear families with ADHD and found the same haplotype was significantly over transmitted to ADHD probands. Screening of the coding region of KCNJ5 in 48 probands with TS did not identify any variation that could explain the association of the haplotype. We also genotyped two microsatellite markers, one in the promoter and the other in the 3′ region and found no evidence for association for either marker for TS, however, we found significant evidence for association with the 3′ repeat and ADHD. A small gene ( c11orf45 ) of unknown function lies within the first intron of KCNJ5 that is transcribed in the opposite orientation and this gene may regulate the expression of KCNJ5 . We studied the correlation of the expression of KCNJ5 and the antisense transcript in brain tissues from control individuals and found that the antisense transcript and the short KCNJ5 isoform are co‐expressed in three brain regions. The results of this study indicate that KCNJ5 is associated with TS and ADHD in our samples, however, the functional variant(s) remain to be identified. Abstract : Linkage and association of Tourette Syndrome (TS) and Attention‐Deficit/Hyperactivity Disorder (ADHD) has previously been reported for chromosome 11q24. We tested for association of the KCNJ5 gene in TS and ADHD and observed biased transmission of haplotypes from parents to probands for both disorders. We screened the gene and promoter and did not identify variants that could explain the association. We also tested for co‐expression of KCNJ5 and a small intronic antisense transcript in brain tissues and found that the antisense transcript and the short KCNJ5 isoform are co‐expressed in three brain regions indicating that this transcript may regulate KCNJ5 expression.